Seismometer Health Diagnosis Based on Cross Spectral Density Coherence Method in Indonesia Seismic Networks - Miftahul Jannah; Risa Annisa; Adhi Harmoko Saputro; Titik Lestari (Program Studi Fisika Universitas Negeri Jakarta, 2024)
Evaluation of seismometer health is crucial in accurately detecting earthquake and tsunami events. Currently, seismometer health evaluation is based solely on data quality unrelated to seismometer sensor performance. While seismometers are essential for tracking seismic activity, environmental factors, aging components, and external interference can cause seismometers to function worse over time. This study presents a seismometer health diagnosis technique based on seismic signal analysis, including signal truncation, signal resampling, filtering, and deconvolution of instrument response. Then the proposed method of cross-spectral density coherence to extract seismometer sensor health indicators performed on two adjacent broadband seismic stations by analyzing the frequency domain with a maximum inter-station distance of 100 km. The data used are seismic signals recorded on three-component seismometers (North-South, East-West, Z-Vertical). The coherence value of cross-spectral density is used as an indicator to diagnose seismometer health. The proposed method was evaluated on a seismic network in Indonesia consisting of 88 stations and a teleseismic earthquake event in Honshu, Japan. The coherence values of almost all tested stations are above 0.8, which means good performance. The proposed method is suitable for analyzing the health of seismometers, especially in Indonesia.